The Spatial Recourses and Limitations of the Russian Economy Modernization: the Example of the North-West Macro Region - Kuznetsov, Sergey Valentinovich; Mezhevich, Nikolay Maratovich; Lachininskii, Stanislav Sergeyevich (Economy of Regions, 2015)
This paper presents the results of the research dedicated to the role of space in the modernization of the economy of the North-West macro-region of Russia conducted in 2012-2014, within the framework of the Presidium of Russian Academy of Sciences (RAS) №31 "The role of space in the modernization of Russia: natural and socio-economic potential." The analysis is based on the methodology, which was developed at the Institute of Regional Economy of RAS. Possibilities of modernization of the Russian economy are due to competitive advantages, "inherited characteristics" and public policy of regions and major macro-regions development. Recourses of modernization have a spatial component, which significantly affects the positioning of the region, its companies, firms and projects in the globalized geo-economic space. It is noted that the characteristics of multi-factor situation, taking into account the “inherited characteristics” of spatial development, the nature of geopolitical and geo-economic situation, transformation of the socio-economic area, evaluation the role of internal and external factors, including the impact of globalization and the state regional policy, as well as assessment of the role of internal spatial inversion of macro-region and innovation potential of regional development mostly define the corridors for modernization of the economy of the regions. It is found that four groups of factors highlighted in this study allow to take into account the wide range of opportunities and constraints for the modernization of the economy of the North-West macro region. On the basis of interdisciplinary synthesis within the geospatial paradigms, taking into account the developments of domestic economists-regionalists, economic geographers and western views in the framework of the space science, the idea of A. I. Tatarkin about "new sources of territorial competitiveness" was confirmed, by the example of a model region of the North-West of Russia. Thus, in the study, based on calculations of the index of integration into the world economy, it is shown that the possibilities of modernization are associated with the degree of openness and competitiveness of regions in the global context. On the example of this macro-region, the space capabilities and limitations of economic modernization, typical for Russia, are identified. Specific ways of the modernization project of the economy of the North-West macro-region are defined, taking into account domestic resources, spatial disparities, “inherited features”, global economic factors, internal constraints and others. The results will be reflected in the implementation of fundamental research of team within the Program of the Presidium of RAS №16 "Spatial Development of Russia in XXI century: nature, society, and their interaction."